Prevalence and determinants of unintended pregnancy among pregnant woman attending ANC at Gelemso General Hospital, Oromiya Region, East Ethiopia: a facility based cross-sectional study - Mohammed, Faiza (BMC Womens Health, 2016)
BACKGROUND: Unintended pregnancy is among the major public health problems that predispose women to maternal death and illness mainly through unsafe abortion and poor maternity care. The level of unintended pregnancy is high in developing countries. Hence, the purpose of this study is to assess the prevalence of unintended pregnancy and the associated factors among pregnant woman attending antenatal care at Gelemso General Hospital, East Ethiopia. METHODS: A facility-based cross-sectional study was conducted from January 10 to April 13, 2015 among women who had attended antenatal care at Gelemso General Hospital. A systematic random sampling technique was used to select a sample of 413 participants. Data were collected via face-to-face interview using a structured and pre-tested questionnaire. Bivariate and multivariate analyses were made to check the associations among the variables and to control the confounding factors. RESULTS: Out of the 413 pregnancies, 112 (27.1 %) were unintended of which 90(21.9 %) were mistimed, and 22(5.2 %) were unwanted. Multivariate analysis revealed that single, divorced/widowed marital statuses, having more than 2 children, and having no awareness of contraception were significantly associated with unintended pregnancy. CONCLUSION: Over a quarter of women had an unintended pregnancy, a rate which is lower than previously reported. Designing and implementing strategies that address contraceptive needs of unmarried, divorced and widowed women, creating awareness of contraceptives at community level and reinforcing postnatal contraceptive counseling to all mothers giving birth at health institution is recommended to reduce the rate of the unintended pregnancy among parous women. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12905-016-0335-1) contains supplementary material, which is available to authorized users.